2000
DOI: 10.1159/000025737
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Uptake Kinetics and Efficacy of New Transfection Reagents: Increase of Oligonucleotide Uptake

Abstract: Human arterial smooth muscle cell (haSMC) proliferation is stimulated by platelet-derived growth factor (PDGF) release of human arterial endothelial cells (haEC) whereas transforming growth factor-β1 (TGF-β1) secretion by haSMC promotes extracellular matrix formation. Inhibitory concepts with antisense oligonucleotides (ASO) against those growth factors might be promising, requiring, however, sufficient transfection efficacy. Thus, toxicity and efficacy of new transfection reagents were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
(60 reference statements)
4
17
0
Order By: Relevance
“…exuberant cell growth and subverted cellular differentiation), numerous studies have been undertaken to demonstrate the utility of retinoids in conferring a desirable SMC or vascular wall phenotype. For example, retinoids can antagonize growth factor-stimulated SMC proliferation in vitro (7)(8)(9)(10)(11)(12), inhibit SMC migration (12,13), and promote a more differentiated SMC phenotype (12, 14 -16). In a series of complementary in vivo studies, retinoids were shown to minimize vascular narrowing following injury to the vessel wall (16 -22).…”
mentioning
confidence: 99%
“…exuberant cell growth and subverted cellular differentiation), numerous studies have been undertaken to demonstrate the utility of retinoids in conferring a desirable SMC or vascular wall phenotype. For example, retinoids can antagonize growth factor-stimulated SMC proliferation in vitro (7)(8)(9)(10)(11)(12), inhibit SMC migration (12,13), and promote a more differentiated SMC phenotype (12, 14 -16). In a series of complementary in vivo studies, retinoids were shown to minimize vascular narrowing following injury to the vessel wall (16 -22).…”
mentioning
confidence: 99%
“…Transfection with the S 3 oligonucleotide resulted in no significant effect as compared with the effect on the control samples, which was the same in regard to protein concentration. Similarly, transfection with vehicle (cytofectin) alone produced a slight decrease (5%) in VEGF mRNA equivalent to that found for the protein reduction and may be reflective of the slight cytotoxic effect known to be associated with cytofectin (21).…”
Section: Resultsmentioning
confidence: 57%
“…The injection technique used has been described previously (21). Briefly, the conjunctiva was cut close to the limbus to expose the sclera, which was then punctured with a 30-guage needle.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown dendrimers to possess toxic side effects both in vitro and in vivo at high doses, but the effects were minimized by optimizing the dose, chemistry and DNA:dendrimer ratio. [22][23][24] Although not yet tested in human trials, no inflammatory response to the injected dendrimer or to the dendrimer plus ODN-1 was observed in our study at any time using ophthalmological examination. In addition, further examination using immunohistochemistry could not detect an increase in the presence of macrophages, which are related to an inflammatory response mediated by toxicity.…”
Section: Discussionmentioning
confidence: 58%